PERBANDINGAN HASIL BELAJAR KORESPONDENSI SISWA YANG DIBERI EVALUASI BENTUK PILIHAN GANDA DENGAN ESSAY TES PADA KELAS X ADMINISTRASI PERKANTORAN DI SMK ERIA MEDAN T.A 2021/2022 - Lastri Lastri; Rijal Rijal (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the Comparison of Correspondence Learning Outcomes of Students who were given Multiple Choice Evaluation with Essay Tests in Class X Office Administration at SMK Eria Medan T.A 2021/2022. This research is experimental, namely research that is intended to determine whether or not there is a result of something caused by the subject, namely students. The population in this study were all students of class X OTKP 1 and OTKP 2 totaling 37 students at SMK Eria Medan. The research sample that will be used in this study is class X OTKP1 and OTKP 2 totaling 37 students. The sampling technique in this study is a purposive sample or a purposive sample. The purpose of the sample is to take the subject, not based on strata, random, or area but based on a specific purpose. In this study, the sample came from class X OTKP-1 which consisted of 17 students and class X OTKP-2 which consisted of 20 students. The analytical technique used is a conformity test using a hypothesis test (t test) to test the comparison of student correspondence learning outcomes who are given a multiple-choice evaluation with an essay test in class X OTKP at SMK Eria Medan T.A 2021/2022. Based on the results of the research that has been done, it can be concluded that there is a significant difference in student learning outcomes in correspondence subjects using multiple choice and essay tests of 5,389 then these results are compared with ttable at a significant level of 5%, namely 1,666. Then tcount > ttable (5,389 > 1,666). From the results of the comparison, it can also be concluded that there are differences in student learning outcomes in correspondence subjects using multiple choice and class X essay tests at SMK Eria Medan.